The role of HLA genes in familial spondyloarthropathy: a comprehensive study of 70 multiplex families. Issue 3 (1st March 2002) - Said-Nahal, R; Miceli-Richard, C; Gautreau, C; Tamouza, R; Borot, N; Porcher, R; Charron, D; Dougados, M; Breban, M
Abstract : Objectives: To investigate whether HLA alleles, other than HLA-B27, influence predisposition to spondyloarthropathy (SpA) in multiplex families. Methods: Seventy French families with at least two affected SpA members were recruited. Patients, and their first degree relatives were typed for HLA-A, B, C, and DR, and extended HLA haplotypes were determined. The distribution of HLA-A, C, and DR alleles carried on HLA-B27+ haplotypes in SpA families was compared with the distribution of these alleles among HLA-B27+ haplotypes in the French general population. Contribution to SpA susceptibility of HLA-A, B, C, and DR alleles, other than HLA-B27, was tested by transmission disequilibrium test. The contribution of HLA alleles to specific presentation features of SpA was examined. Results: Frequencies of HLA-A, C, and DR alleles carried on HLA-B27+ haplotypes from SpA families were comparable with those seen in the French population, except for DR13 which was overrepresented among patients (pcorr<0.001). Most interestingly, the HLA-DR4 allele was transmitted in excess to patients with SpA, independently of linkage to HLA-B27 (pcorr=0.05), and in a direction opposite to that for HLA-B27+ unaffected siblings (pcorr=0.01). Finally, the distribution of HLA alleles was not related to the presentation feature of SpA. Conclusion: HLA predisposition to familial SpA appears not to be limited to HLA-B27, but some HLA-DR alleles also have a significant influence. In particular, HLA-DR4 contributes significantly to a genetic predisposition to SpA, which may have implications in our understanding of SpA pathogenesis.